2022
DOI: 10.3390/cells11020206
|View full text |Cite
|
Sign up to set email alerts
|

CerS1 but Not CerS5 Gene Silencing, Improves Insulin Sensitivity and Glucose Uptake in Skeletal Muscle

Abstract: Skeletal muscle is perceived as a major tissue in glucose and lipid metabolism. High fat diet (HFD) lead to the accumulation of intramuscular lipids, including: long chain acyl-CoA, diacylglycerols, and ceramides. Ceramides are considered to be one of the most important lipid groups in the generation of skeletal muscle insulin resistance. So far, it has not been clearly established whether all ceramides adversely affect the functioning of the insulin pathway, or whether there are certain ceramide species that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…This is similar to the observation in humans where obese, insulin-sensitive individuals have similar levels of Cer18:0 to lean individuals, while obese, insulin-resistant individuals had increased levels ( Tonks et al, 2016 ). Previous studies have also shown Cer18:0 content in muscle to be increased in mice fed a Hi-F diet ( Turner et al, 2013 ; Turpin-Nolan et al, 2019 ; Frangioudakis et al, 2010 ) while reductions of Cer18:0, through deletion of ceramide synthase 1, has been associated with improved glucose tolerance and insulin sensitivity ( Turpin-Nolan et al, 2019 ; Błachnio-Zabielska et al, 2022 ). Our data also showed a negative correlation between skeletal muscle insulin sensitivity (insulin-stimulated glucose uptake) and muscle Cer18:0 levels.…”
Section: Discussionmentioning
confidence: 90%
“…This is similar to the observation in humans where obese, insulin-sensitive individuals have similar levels of Cer18:0 to lean individuals, while obese, insulin-resistant individuals had increased levels ( Tonks et al, 2016 ). Previous studies have also shown Cer18:0 content in muscle to be increased in mice fed a Hi-F diet ( Turner et al, 2013 ; Turpin-Nolan et al, 2019 ; Frangioudakis et al, 2010 ) while reductions of Cer18:0, through deletion of ceramide synthase 1, has been associated with improved glucose tolerance and insulin sensitivity ( Turpin-Nolan et al, 2019 ; Błachnio-Zabielska et al, 2022 ). Our data also showed a negative correlation between skeletal muscle insulin sensitivity (insulin-stimulated glucose uptake) and muscle Cer18:0 levels.…”
Section: Discussionmentioning
confidence: 90%
“…Calcification of the AV is a fundamental mechanism in the development of AVS 4,35 . In general, ceramides influence calcification, but the specific role of CerS5 has not been investigated yet 20,31,36 . Our work shows that inhibition of CerS5 leads to reduced calcification of VICs in vitro.…”
Section: Discussionmentioning
confidence: 59%
“…The impact of ceramides on obesity and lipid metabolism is well studied 14,31,32 . It has been shown that CerS5 is essential to maintain systemic C16 ceramide levels in mice 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the observation in humans where obese, insulin-sensitive individuals have similar levels of Cer18:0 to lean individuals, while obese, insulin-resistant individuals had increased levels [4]. Previous studies have also shown Cer18:0 content in muscle to be increased in mice fed a HFD [9; 21; 23] and reductions of Cer18:0 through deletion of ceramide synthase 1 (CerS1), has been reported to improve glucose tolerance and insulin sensitivity [21; 24]. Our data also showed a negative correlation between skeletal muscle insulin sensitivity (insulin-stimulated glucose uptake) and muscle Cer18:0 levels.…”
Section: Discussionmentioning
confidence: 99%